An analysis of digitalization and firm performance in Finland's private service industries - Kuosmanen, Natalia,Pajarinen, Mika,Heshmati, Almas (Taloustieto Oy, 2024)
The service sector is undergoing rapid changes attribut- ed to digitalization. This study examines the relation- ship between digitalization and the performance of the Finnish private service firms from 2015 to 2021 using linked employer-employee data, financial data and an IT usage survey. Our descriptive and regression anal- yses reveal significant variability in the level and areas of digital adoption across service industries. Informa- tion and communication, and professional activities are found highly digitalized, while accommodation and food service activities, and transportation and storage lag in digitalization intensity. Additionally, we find a strong positive correlation between firms' digitalization and revenues, particularly for firms with higher digital inten- sity. This correlation persisted throughout the COVID-19 pandemic. We also observe a positive correlation be- tween digitalization and productivity in the early years, but more recent data suggest a weakening of this associ- ation, possibly due to increased digital adoption among less productive firms during the pandemic. Finally, our analysis indicates that larger firms, or those with a larg- er market share or international activities, tend to have higher levels of digitalization. Thus, investment in digi- talization is recommended to enhance service sectors performance.
10419/301845
Keywords: Graue Literatur; Digitalization; Firm performance; Productivity; Private service industry; Finland